The Heterogeneous Cost of Wage Rigidity: Evidence and Theory - Ester Faia; Vincenzo Pezone (Leibniz Institute for Financial Research SAFE, 2020)
Using a unique confidential contract level dataset merged with firm-level asset price data, we find robust evidence that firms' stock market valuations and employment levels respond more to monetary policy announcements the higher the degree of wage rigidity. Data on the renegotiations of collective bargaining agreements allow us to construct an exogenous and accurate measure of wage rigidity. The amplification induced by wage rigidity is stronger for firms with high labor intensity and low profitability. There are clear distributional consequences of monetary policy. We rationalize the evidence through a model in which firms in different sectors feature different degrees of wage rigidity due to staggered renegotiations vis-a-vis unions.
Keywords: 330; heterogeneous monetary policy response; distributional consequences of monetary policy; employer-employee level dataset; monetary policy surprise shocks; heterogeneous wage rigidity